PENGARUH PEMBERDAYAAN DAN KEPERCAYAAN TERHADAP TANGGUNG JAWAB KEPALA SEKOLAH DASAR NEGERI KECAMATAN PULOGADUNG JAKARTA TIMUR - Theresia Supartinah (Jurnal Manajemen Pendidikan, 2015)
This study provides information on the effect of empowerment and trust in the responsibility of the principal at SDN Pulogadung, East Jakarta. The method used in this research is the survey method using a quantitative approach, and explain the causal relationship with path analysis. Data were collected by questionnaire. The target population of this study amounted to 92 principals of all Heads of State Primary School in District of Pulogadung in East Jakarta. In this study a sample set of 75 people, using simple random sampling. Results from this study indicate that: (1) there is a positive direct effect of the empowerment to responsibility, (2) there is a positive direct effect of trust to the responsibility, and (3) there is a positive direct effect of trust to empowerment.